2021
DOI: 10.1097/pec.0000000000002489
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Elevated Social Risk in Pediatric Emergency Department Patients and Families

Abstract: This study aimed to identify predictors of high unmet social needs among pediatric emergency department (ED) patients. We hypothesized that obesity, frequent nonurgent visits, reported food insecurity, or an at-risk chief complaint (CC) would predict elevated social risk. Methods:We administered a tablet-based survey assessing unmet social needs in 13 domains to caregivers of patients aged 0 to 17 years presenting to an urban pediatric ED. Responses were used to tabulate a social risk score (SRS). We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Liberman et al [51] demonstrated the pediatric ED setting could provide successful referrals as a result of screeners, with over 90% of families reporting satisfaction with services received. Although the ED offers one such potential setting for screening [52], these visits and provider relationships are limited to what is often a brief encounter.…”
Section: Acute Care Settingsmentioning
confidence: 99%
“…Liberman et al [51] demonstrated the pediatric ED setting could provide successful referrals as a result of screeners, with over 90% of families reporting satisfaction with services received. Although the ED offers one such potential setting for screening [52], these visits and provider relationships are limited to what is often a brief encounter.…”
Section: Acute Care Settingsmentioning
confidence: 99%
“…Increased social needs screening in emergency departments (ED) is supported by recent literature reporting high rates of unmet social needs, their health and wellness impact, and numerous policy statements on poverty by the American Academy of Pediatrics (AAP) 1‐13 . Pediatric emergency physicians report a high perceived value of social needs screening and intervention, yet few feel prepared to address this need largely due to lack of time and training 11,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased social needs screening in emergency departments (ED) is supported by recent literature reporting high rates of unmet social needs, their health and wellness impact, and numerous policy statements on poverty by the American Academy of Pediatrics (AAP). [1][2][3][4][5][6][7][8][9][10][11][12][13] Pediatric emergency physicians report a high perceived value of social needs screening and intervention, yet few feel prepared to address this need largely due to lack of time and training. 11,14,15 Rather than looking to advocacy efforts provided by individual health care workers, there is now a call for the integration of social care-services that address health-related social risk factors and social needs-into clinical practice and training at the health care system level.…”
Section: Introductionmentioning
confidence: 99%
“…2 Social risks (e.g., housing and food insecurity, inadequate access to preventative health care) are prevalent among emergency department (ED) patients. [3][4][5] Such social determinants of health are associated with poor health outcomes, including higher rates of ED utilization, hospitalization, and mortality. [6][7][8][9] By including social determinants of health in the assessment of medical complexity and risk, the new coding guidelines take an important step in recognizing the multifaceted care provided in the ED.…”
mentioning
confidence: 99%
“…As providers of safety net health care, emergency medicine providers are intimately aware of the important role that social risk plays in patients' lives and, thus, in the medical decision‐making process 2 . Social risks (e.g., housing and food insecurity, inadequate access to preventative health care) are prevalent among emergency department (ED) patients 3–5 . Such social determinants of health are associated with poor health outcomes, including higher rates of ED utilization, hospitalization, and mortality 6–9 .…”
mentioning
confidence: 99%